Fmr1-Deficiency Impacts Body Composition, Skeleton, and Bone Microstructure in a Mouse Model of Fragile X Syndrome - Leboucher, Antoine; Bermudez-Martin, Patricia; Mouska, Xavier; Amri, Ez-Zoubir; Pisani, Didier F.; Davidovic, Laetitia (Frontiers in Endocrinology, 2019)
Fragile X syndrome (FXS) is a neurodevelopmental disorder associated with intellectual disability, hyperactivity and autism. FXS is due to the silencing of the X-linked FMR1 gene. Murine models of FXS, knock-out (KO) for the murine homologue Fmr1, have been generated, exhibiting CNS-related behavioural and neuronal anomalies reminiscent of the human phenotypes. As a reflection of the ubiquitous expression of the FMR1 gene, FXS is also accompanied by physical abnormalities. This suggests that the FMR1-deficiency could impact skeletal ontogenesis. In the present study, we highlight that Fmr1-KO mice display changes in body composition with an increase in body weight, likely due to both increase of skeleton length and muscular mass along with reduced visceral adiposity. We also show that, while Fmr1-deficiency has no overt impact on cortical bone mineral density, cortical thickness was increased and cortical eccentricity was decreased in the femurs from Fmr1-KO mice as compared to controls. Also, trabecular pore volume was reduced and trabecular thickness distribution was shifted towards higher ranges in Fmr1-KO femurs. Finally, we show that Fmr1-KO mice display increased physical activity. Although the precise molecular signalling mechanism that produces these skeletal and bone microstructure changes remains to be determined, our study warrants further investigation on the impact of FMR1-deficiency on whole-body composition, as well as skeletal and bone architecture.